P2-S1.05 Parental acceptability of contraceptive methods offered to their teen during a confidential healthcare visit. (10th July 2011) - Hartman, L; Shafer, M A; Pollack, L; Wibbelsman, C; Chang, F; Tebb, K
Abstract : Background: STIs remain epidemic among teens. Parents have a powerful influence on their teens' sexual behaviours, yet their role in preventing adolescent STIs and unplanned pregnancies has been largely ignored in clinical practice and research. Objective: To explore parental acceptability of different contraceptive methods, including condoms, offered to their teen during a confidential healthcare visit (CV). Methods: A cross-sectional phone survey of 261 randomly selected parents/caregivers of girls 12–17 years enrolled in two large diverse clinic systems. Parental acceptability of 7 different contraceptive methods was assessed on a 4-point likert scale (1=very unacceptable to 4=very acceptable). We examined if parental acceptability varied according to a variety of demographic factors, perceived likelihood of teen's sexual activity, and parental knowledge of STIs using bivariate analyses (χ 2 for categorical correlates, t tests for continuous correlates). Results: Parents surveyed were 27–69 years old (mean 45 yrs), 70% married; 86% female; and diverse (46% Latino, 23% White, 16% Black, 11% Asian, 3% Other). 15% of household incomes were 20 K or less and 25% over 100 K. 36% attended religious services at least once/week. When parents were asked about their own experiences as teens, 40% reported sexual intercourse, 4% had an STI, 14% had a teen pregnancy, and 25% used birth control. The majority of parents lacked STI knowledge (56% correctly answered 0-1 out of 5 basic knowledge questions). Overall acceptability of contraception provided to their teen was highest for oral contraceptive pills (OCP) 59% and condoms 51% and lowest for IUDs 18% (see Abstract P1-S2.05 table 1 ). Only 24% thought there was any likelihood their teen would have sexual intercourse in the next year. Acceptability of OCPs, condoms, and emergency contraception was higher among parents who report a likelihood their teen would have sex. Discussion: This is the first study to examine parental acceptability of contraception offered during a CV. This study shows that parents lack basic STI knowledge and underestimate their teens' sexual activity. Only half found condoms, the only method that offers both STI and contraception protection, to be acceptable. In the context of providing confidential health services for teens, these findings highlight the need to better understand influences on parental attitudes and to improve communication with parents about sexual health topics, STIs, and condom use.